Bis{4-chloro-2-[2-(1H-indol-3-yl)ethyliminomethyl]phenolato-κ2 N,O}zinc(II) - Ali, Hapipah Mohd; Mohamed Mustafa, M.I.; Rizal, Mohd Razali; Ng, Seik Weng (International Union of Crystallography, 2008)
The Zn atom in the title compound, [Zn(C17H14ClN2O)2], is N,O-chelated by two deprotonated Schiff base monoanionic ligands in a tetrahedral coordination geometry. The Zn atom lies on a special position of site symmetry 2.